Creators, multipliers, and lurkers: who contributes and who benefits at online review sites. Issue 1 (11th March 2014) - Munzel, Andreas; H. Kunz, Werner
Abstract : Purpose: – As the internet has become an increasingly relevant communication and exchange platform, social interactions exist in multiple forms. The research aims to integrate a multitude of those interactions to understand who contributes and why different types of contributors generate and leverage social capital on online review sites. Design/methodology/approach: – Based on the literature about social capital, social exchange theory, and transformative consumer research, the authors carried out a study of 693 contributors on a hotel review site. Content analysis and a latent profile analysis were used to research the contribution types and the underlying motives for generating and leveraging social capital. Findings: – Through the integration of various customer-to-customer interactions, the results reveal a three-class structure of contributors on review sites. These three groups of individuals show distinct patterns in their preferred interaction activities and the underlying motives. Research limitations/implications: – The authors develop the existing literature on transmission of electronic word-of-mouth messages and typologies of contributors. Future research should seek to expand the findings to additional industry and platform contexts and to support the findings through the inclusion of behavioral data. Originality/value: – The research contributes to researchers and marketers in the field by empirically investigating who and why individuals engage in online social interactions. The authors expand upon the existing literature by highlighting the importance of social debt in anonymous online environments and by assessing a three-class structure of online contributors.